Analisis Ukuran Partikel Serbuk Arang terhadap Pengurangan Kadar Abu pada Briket Tempurung Kelapa - Napitupulu, Robert; Pratama, Randa Julio; Dharta, Yuli (Politeknik Negeri Lhokseumawe, 2025)
As an environmentally friendly alternative fuel, coconut shell briquettes have the potential to replace fossil fuels. However, the main challenge in its use is the high ash content that reduces combustion efficiency and produces residues that are difficult to clean. This study focuses on analyzing the effect of charcoal particle size on reducing ash content in coconut shell briquettes. The method used was a full factorial experimental design with two process variables: the ratio of charcoal powder and tapioca starch (90%:10%, 85%:15%, 80%:20%), and charcoal particle size (40, 60, and 80 Mesh). To improve accuracy, each treatment combination was repeated three times. The stages of making briquettes include material preparation, mixing, molding, and drying. Ash content testing was conducted in accordance with SNI 01-6235-2000 standard. The results showed that charcoal particle size has a significant effect on ash content, where larger particles produce lower ash content. The lowest ash content, 1.49%, was found in briquettes with 40 Mesh particle size. This study makes an important contribution to the development of more efficient and environmentally friendly coconut shell briquettes.